The contract - Seymour, Gerald (New York : Holt, Rinehart and Winston, 1980)
Discharged from the army, Johnny Donoghue is eager to earn his redemption. His assignment is to infiltrate East Germany and arrange the defection of a top-flight scientist working on the Russian missile systems. But no one warned Johnny of the traps in store.
Keywords: Spy -- Detective